2015
DOI: 10.1021/acsnano.5b05281
|View full text |Cite
|
Sign up to set email alerts
|

Binary Crystallized Supramolecular Aerogels Derived from Host–Guest Inclusion Complexes

Abstract: Aerogels with low density and high porosity show outstanding properties such as large surface area and low thermal and acoustic conductivity. However, great challenges remain to convert hydrophilic polymer based hydrogels to corresponding aerogels. Here, we report a structurally new type of aerogels, supramolecular aerogels (SMAs), derived from supramolecular hydrogels formed by self-assembling of poly(ethylene glycol) and α-/γ-cyclodextrin. The SMAs posses a characteristic binary crystallized nanosheet struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
60
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 56 publications
0
60
0
1
Order By: Relevance
“…Porous materials, such as covalent organic frameworks (COF), [1,2] Metal-organic frameworks (MOF), [3,4] zeolites, [5,6] mesoporous silica, [7,8] aerogels, [9][10][11] and sponges, [12,13] have received considerable attentions in recent years due to their crucial applications in gas storage, absorption, separation, catalysis, sensing, energy, thermal insulation, and biomedicine etc. The physical properties and applications of the porous materials mostly rely on their pore parameters, [14,15] such as pore size, pore volume, porosity, regularity, and dispersity, [16][17][18] and can be tuned by different synthesis methods.…”
Section: Introductionmentioning
confidence: 99%
“…Porous materials, such as covalent organic frameworks (COF), [1,2] Metal-organic frameworks (MOF), [3,4] zeolites, [5,6] mesoporous silica, [7,8] aerogels, [9][10][11] and sponges, [12,13] have received considerable attentions in recent years due to their crucial applications in gas storage, absorption, separation, catalysis, sensing, energy, thermal insulation, and biomedicine etc. The physical properties and applications of the porous materials mostly rely on their pore parameters, [14,15] such as pore size, pore volume, porosity, regularity, and dispersity, [16][17][18] and can be tuned by different synthesis methods.…”
Section: Introductionmentioning
confidence: 99%
“…Thed egree of polymerization (n)o fP VDMMS is as high as 91. There is no peak or absorption band corresponding to vinyl groups observed in the 29 Si CP/MAS NMR (Figure 2a) or FTIR ( Figure S1) spectra, indicating the high conversion of PVDMMS and PVDMMS/PVMDMS.…”
mentioning
confidence: 99%
“…However,t raditional aerogels are usually dried via costly supercritical drying (SCD) and exhibit low mechanical strength because of their intrinsically fragile/brittle networks,w hich need to be addressed before their practical applications.To overcome the costly drying process and brittleness, many efforts have been made to lower the cost by ambient pressure drying (APD), [23] freeze drying (FD) [22] and vacuum drying (VD), [24] and reinforce the aerogels by av ariety of methods.C ross-linking of aerogels with organic polymers is aw idely used method to reinforce the aerogels but usually results in lower porosity and higher density that limit their applications. [25,26] Flexible polymer-based aerogels can be obtained from resorcinol-formaldehyde, [27] poly(vinyl alcohol), [28] and supramolecules, [29] and some of them exhibit good absorption of organic solvents/oils.A nother kind of aerogels based on biomass such as nanocellulose and chitosan with compressibility and bendability have been reported. [30,31] Owing to their highly porous nanostructure that is composed of nanofibers,t hey show excellent thermal insulation performances.B esides,a ssembly of nanofibers via as pecific method can give compressible and elastic cellular aerogels with high pressure-sensitivity and good absorption/separation properties.…”
mentioning
confidence: 99%
“…[22][23][24] Unlike the polysiloxane-based organic-inorganic hybrid aerogels, however, they do not show elastic recovery in response to compression and bending. It is reported that polymer-based aerogels such as supramolecular aerogel, 25 poly(vinyl alcohol)-based aerogel, 3 thermoelectric polymer aerogel 26 and resorcinol-formaldehyde aerogel 27 exhibit high mechanical strength or elasticity against compression. Nonetheless, almost all of them are mainly composed of macropores and are opaque in visible light region.…”
Section: Introductionmentioning
confidence: 99%